2005
DOI: 10.1007/bf03023087
|View full text |Cite
|
Sign up to set email alerts
|

Epidural blood patch - myths and legends

Abstract: PIDURAL blood patch (EBP) was suggested before even I was born, and has been considered the most effective treatment of post-dural puncture for over 40 years, yet many aspects still fascinate and confuse, and its clinical merit remains controversial. A systematic review of EBP, in the highly respected Cochrane database of systematic reviews, concluded: " At present, except in the context of a randomised controlled trial, we believe that epidural blood patching should be reserved for exceptional cases only (suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…In summary, it seems a volume of 10 to 20 mL is deemed an appropriate volume for EBP in the literature, with reasonable success rates of 60% to 75% and very few complications [3,4]. However, because the rate of complications is low, one would need to study thousands of patients to find a single serious consequence of the procedure [7]. One other case described a spinal subdural hematoma with a volume greater than 30 mL [11].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In summary, it seems a volume of 10 to 20 mL is deemed an appropriate volume for EBP in the literature, with reasonable success rates of 60% to 75% and very few complications [3,4]. However, because the rate of complications is low, one would need to study thousands of patients to find a single serious consequence of the procedure [7]. One other case described a spinal subdural hematoma with a volume greater than 30 mL [11].…”
Section: Discussionmentioning
confidence: 96%
“…Degree of CSF loss or dural damage from the initial "wet tap" may influence the success of EBP at any volume. In addition, timing seems to be a very important factor; initial EBPs performed a full 24 hours following dural puncture are more successful [7], even when relatively smaller volumes of blood are used [8].…”
Section: Introductionmentioning
confidence: 99%
“…The most common complication of EBP is immediate or late back pain. 8 In a long-term follow-up study, 35% of patients reported back pain that subsided within 48 h. 9 This may result from the leakage of blood into the intervertebral ligaments and subcutaneous fat. 7 Rare complications include lower back pain with radicular pain, spinal subdural hematoma, spinal subdural epiarachnoid hematoma (complication of a novel technique involving intentional puncture of the dura), intrathecal hematoma and arachnoiditis, and two cases of neurologic deterioration after EBP to patients with increased intracranial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…However, a more extensive investigation with radiological imaging should be considered in cases with less typical symptoms or headache persisting after a first correctly performed EBP. As EBP has been associated with serious complications (2–5), anaesthetists should be more critical when asked to perform this procedure in patients with symptoms inconsistent with PDPH, or when a first procedure has failed. Fortunately, the two EBPs in our patient did not result in catastrophic deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, complications may be serious. Aseptic arachnoiditis and meningitis, intracranial hypertension, cauda equina syndrome, bradycardia, pneumocephalus and subarachnoid haematoma have all been described (2–5). Repeat EBP may be necessary in a small percentage of patients.…”
mentioning
confidence: 99%